The conceptualization of 'space' in Persian and English: A comparative study - Raheleh Gandomkar; Setareh Parvinnia (نشریه پژوهش‌های زبان‌شناسی)
This article aims at contrasting the conceptualization of space in Persian and English. Using three semantic primes of 'space', namely 'below', 'side' and 'touch' proposed in Natural Semantic Metalanguage (NSM), as one of the cognitive semantics approaches to study language, this cross-linguistic design intends to uncover the similarities and differences of conceptualizations in the two languages. The data came from the Hamshahri corpus of Persian-written data and the Corpus of Contemporary American English (COCA).The data were compared to see whether or not the NSM theory is viable to explain the spatial conceptualization. The results indicated that the semantic primes have more than one exponent in Persian and English, with their particular function and conceptual range. Besides, the prime of 'touch' has not spatial correspondence in Persian language. This means that the NSM approach does not provide enough analytical toolkits to satisfactorily explain the similarities and differences in cross-cultural cognitive semantic comparisons and cannot exhaustively explain the conceptualization of ‘space’. Nonetheless, this approach provides us with some insight into the cognitive properties in the minds of the speakers.